2019
DOI: 10.3390/genes10060412
|View full text |Cite
|
Sign up to set email alerts
|

The Polyubiquitin Gene MrUBI4 Is Required for Conidiation, Conidial Germination, and Stress Tolerance in the Filamentous Fungus Metarhizium robertsii

Abstract: The polyubiquitin gene is a highly conserved open reading frame that encodes different numbers of tandem ubiquitin repeats from different species, which play important roles in different biological processes. Metarhizium robertsii is a fungal entomopathogen that is widely applied in the biological control of pest insects. However, it is unclear whether the polyubiquitin gene is required for fungal development, stress tolerance, and virulence in the entomopathogenic fungus. In the present study, the polyubiquit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…Therefore, the Δ Mr-abaA mutant showed significantly increased sensitivity to heat stress. Furthermore, some key heat-stress-responsive genes were assessed for their transcript levels in the Δ Mr-abaA mutant, relative to the WT strain ( 32 , 33 ). qRT-PCR results indicated that the heat stress significantly downregulated 2 of 4 genes involved in the glycolytic pathway, 5 of 11 genes encoding heat shock proteins, and 2 of 5 catalase genes but remarkably upregulated 3 of 6 genes involved in the pyruvate-consuming pathway in the Δ Mr-abaA mutant ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the Δ Mr-abaA mutant showed significantly increased sensitivity to heat stress. Furthermore, some key heat-stress-responsive genes were assessed for their transcript levels in the Δ Mr-abaA mutant, relative to the WT strain ( 32 , 33 ). qRT-PCR results indicated that the heat stress significantly downregulated 2 of 4 genes involved in the glycolytic pathway, 5 of 11 genes encoding heat shock proteins, and 2 of 5 catalase genes but remarkably upregulated 3 of 6 genes involved in the pyruvate-consuming pathway in the Δ Mr-abaA mutant ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In case of Metarhizium robertsii (fungal entomopathogen), a study was conducted on polyubiquitin gene ( MrUBI4 and MAA_02160). The gene deletion in the experimental strains showed significant reduction in conidial yields and delay in conidial germination as compared with control strains (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the polyubiquitin gene CpUBI4 is required for fungal development, stress adaptation, and virulence in Cryphonectria parasitica , a phytopathogenic filamentous fungus that causes chestnut blight disease ( Chen et al., 2018 ). The role of polyubiquitin genes in insect fungal pathogens were also explored recently ( Wang et al., 2019b ; Wang et al., 2020 ). Polyubiquitin genes were functionally characterized via gene deletion in Metarhizium robertsii and Beauveria bassiana .…”
Section: Ubiquitinmentioning
confidence: 99%
“…Polyubiquitin genes were functionally characterized via gene deletion in Metarhizium robertsii and Beauveria bassiana . MrUBI4 is involved in UV stress and the heat-shock response in M. robertsii ( Wang et al., 2019b ). Deletion of UBI4 leads to a defect in stress tolerance and attenuated virulence in B. bassiana ( Wang et al., 2020 ).…”
Section: Ubiquitinmentioning
confidence: 99%